Comparison of transmittance and reflectance mode of FT MIR and FT NIR spectroscopy in application to clarified milk fat - Mehta, Bhavbhuti M. (Indian Journal of Dairy Science, 2016)
The clarified/anhydrous milk fat (ghee) is by far the most ubiquitous traditional fat rich dairy product of India. Traditional chemical methods for characterization and authentication of edible oils and fats are very time consuming, highly laborious and costly. Infrared spectroscopy based techniques are gaining their acceptance for analysis of edible oils and fats. Comparative appraisal for transmittance and reflectance modes of FT MIR and FT NIR spectroscopy in application to fat and oil appears to be not reported. In present study quality of the spectra of cow and buffalo ghee samples were obtained from FT MIR and FT NIR transmittance spectroscopy as well as reflectance spectroscopy were evaluated. FT MIR spectra of ghee obtained from reflectance mode using Horizontal Attenuated Total Reflectance (HATR) were prominent, intense, sharp, clearly defined, with well resolved peaks and free from anomalies such as interference fringes and baseline shift. In case of FT NIR spectroscopy of ghee, the spectra obtained from transmittance mode were found better in quality compared to those obtained from transmittance mode. Therefore, in of anhydrous milk fat like ghee use of FT MIR spectroscopy in reflectance mode using HATR crystal and FT NIR spectroscopy in transmittance mode is recommended.